Physicochemical and thermal characterization and antioxidant property of chicken feather keratin and ginger starch hybrid nanocomposite film - Olarewaju M. Oluba; Deborah A. Edeh; Samuel I. Ojeaburu; Opeyemi A. Bayo-Olorunmeke; Sunday J. Josiah (Carbohydrate Polymer Technologies and Applications, 2023)
The fabrication of starch-based nanocomposites is regarded as a sustainable method of manufacturing ecologically favourable packaging materials in addition to their better gaseous barrier attribute over starch films. The present study assessed the physicochemical and thermal characterization as well as antioxidant property of a starch-keratin nanocomposite blend fabricated from ginger starch and chicken feather keratin. Starch-keratin nanocomposite films composed of 90:10 and 70:30 ginger starch:chicken feather keratin were fabricated and analysed. The physicochemical characteristics such as moisture content, transparency, water solubility, and water vapour permeability decreased significantly by 22.67 %, 15.06 %, 12.95 %, and 1.40 %, respectively, with a higher keratin level in the film. The tensile strength by 18.84 % with increasing starch content, while the elongation at break was highest in the 90:10, followed by 70:30 film and starch film without keratin, respectively. The absorption spectra representing OH vibrational stretching band in ginger starch was shifted from 3252.4 cm−1 (S) to 3296.4 cm−1 (S-K, 90:10) and 3294.6 cm−1 (S-K, 70:30) while the CH stretching vibration was shifted from 2929.6 cm−1 (S) to 2928.4 cm−1 (S-K, 90:10) and 2923.5 cm−1 (S-K, 70:30). The degree of amorphousity of the film increased with increasing keratin content. The optimum degradation temperatures was reduced from 244.0 °C to 236.8 °C with increasing keratin content. The crystallisation temperature in the starch-keratin nanocomposite film, though higher than those of starch and keratin, was reduced from 286.3 °C (S-K, 70:30) to 266.0 °C (S-K, 90:10). The antioxidant property of the film was significantly higher in the 70:30 film compared to 90:10. Overall, the starch-keratin nanocomposite film presented improved physicochemical and thermal attributes compared to the starch-only film.